Using games to disrupt the conference Twittersphere - Rosie Jones; Emily Shields (Association for Learning Technology, 2018)
Social media tools are changing practices in many industries, including academia, and the Twitter platform is widely recognised as the 'tool of choice' for microblogging. Academic conferences often use social media to provide conference 'backchannels'. This article describes a conference game using toys as alter egos, driven through Twitter. We found that the soft toy game format was participated in by a majority of the attendees, with early posts in advance of the conference a good signal of engagement. We look at what the organisers learnt from the game and how such games, including Twitter elements, could support wider networks beyond the conference itself.